Taxation and State Participation in Nigeria's Oil and Gas Sector - World Bank (Washington, DC, 2014)
Oil and gas are critical to Nigeria's economic and social performance. Oil alone accounts for 40 percent of the country's GDP, 70 percent of budget revenues, and 95 percent of foreign exchange earnings. Nigeria's dependence on petroleum is much greater than that of many other major producing countries. 2. Taxation and state participation are both designed to deliver benefits from the petroleum sector to the state and are the subject of this report. This report is based on Bank staff missions to Nigeria in January and July 2000. Principal conclusions and recommendations are also included in this report.